Fear of Failure and Entrepreneurial Intention: Evidence from STIE Ganesha Students - Hadi Sutrisno; Sukardi Sukardi (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study examines fear of failure as a psychological barrier to entrepreneurial intention among students at STIE Ganesha and identifies factors shaping their risk perception. A qualitative phenomenological approach was employed, involving 12 undergraduate students (semesters 4–8) selected through purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke’s thematic analysis. The findings show that 100% of informants experienced fear of failure, primarily in the form of fear of financial loss (83%), fear of social stigma (75%), and self-doubt (67%). Risk perception is influenced by overprotective family communication, exposure to negative business narratives on social media, and limited practical training in risk management. These results indicate that fear of failure is shaped not only by individual psychological factors but also by social and educational contexts. The study implies the importance of integrating risk management training and psychological coping strategies into entrepreneurship education, along with mentoring programs involving experienced entrepreneurs to strengthen students’ entrepreneurial readiness.